The influence of tumour progression on serum concentration of HER2 receptor extracellular domain and metalloproteinase 9 in patients with uterine cervical cancer - Kopczyńska, Ewa; Makarewicz, Roman; Biedka, Marta; Kardymowicz, Hanna; Tyrakowski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2008)
Background: HER2 receptor extracellular domain is proteolytically cleaved from the receptor by means of metalloproteinases. Increased serum concentrations of both HER2 ectodomain and metalloproteinase 9 are observed in various tumour types. Aim of the study: The aim of this study was to estimate serum HER2 ectodomain and MMP-9 concentration in relation to clinicopathological features (findings) in patients with uterine cervical cancer and to assess the correlation between concentrations of these proteins. Material and methods: The study group consisted of 40 patients with cervical cancer ranging in age from 30 to 79 years (mean age 52.4±12.1). Serum ECDHER2 and MMP-9 concentrations were evaluated by ELISA. Results: Serum concentration of both ECDHER2 and MMP-9 was significantly higher in cervical cancer patients than in controls. The concentration of ECDHER2 was higher in patients with stage I than III (FIGO staging) and in the subgroup with stage I-II than with stage II-IV, and higher in patients with operable tumour than in inoperable. MMP-9 concentration increased together with tumour stage. It was significantly higher in patients with stage III than I and in the subgroup of patients with tumour advanced distantly (III-IV) than advanced locally (I-II), and it was higher in patients with tumour infiltrated sites behind the cervix uteri (II-IV) than in patients with tumour limited to the cervix uteri (I). ECDHER2 concentration was increased in 67.5% of patients, compared to MMP-9 concentration in 37.5%. Two markers, ECDHER2 and MMP-9, showed a weak negative correlation (r=–0.19). Conclusions: In uterine cervical cancer patients the concentration of ECDHER2 decreases with tumour progression, while concentration of MMP-9 increases.